Are state unemployment insurance reserves sufficient for the next recession? - Christopher J. O'Leary; Kenneth J. Kline (W.E. Upjohn Institute for Employment Research, 2016)
Regular state unemployment insurance (UI) benefits are paid from state reserves held in unemployment trust fund accounts at the U.S. Treasury. Employers covered by the federal-state UI system make contributions to reserve accounts based on taxable wages. The federal government provides incentives for forward funding of benefits to support UI as an automatic macroeconomic stabilizer in the economy. However, the Great Recession exhausted UI reserves for the majority of states, and not all of them have yet replenished those reserves. Based on patterns observed over the past 40 years, in this paper we simulate the effects on state and systemwide reserves supposing that a mild, moderate, or severe recession emerges in the coming months. Our results suggest that even a moderate recession would cause a majority of states to exhaust UI reserves and be forced to borrow to pay regular UI benefits. We note that recent experience with federal funding of extended and emergency benefits may have contributed to the current state UI financing posture, and we suggest that the taxable wage bases are insufficient. The UI system exists to help involuntarily jobless Americans while they are between jobs. By accepted standards of adequacy, benefit provisions are not excessive, but limits in the financing system make it slow to recover from debt. State reserve funds have not yet reached levels sufficient to weather another economic storm.
Keywords: H71; H81; J65; 330; Unemployment insurance; benefit financing; forward funding; taxable wage base; reserve ratio; adequate reserves; average high-cost rate; federal loans; state revenue bonds